Ajaran Sarengat, Tarekat, Hakekat, dan Makrifat Dalam Serat Jasmaningrat - Umi Masfiah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
Javanese manuscripts consist of Islamic teaching which are told as stories. One of those manuscripts is Serat Jasmaningrat kept in Kawedanan Ageng Punakawan Widya Budaya Yogyakarta palace. The plot and figures in the story are ways to explain religious concepts such as syari’at, tarekat, hakikat and makrifat. Those concepts are explained in the manuscript as a name of person like Ki Sarengat, Ki Tarekat, Ki Hakekat, and Ki Makrifat. There are other figures as personification of other spiritual concepts such as Ki Duhur, Ki Asyar, Ki Maghrib, Ki Isya, Ki Subuh, and Minalwitri, Ki Kalbu, Ki Jiwa, Ki Pramana, Ki Budi, Ki Panrima, Ki Tapsila, Ki Eling and so forth. This research uses content analysis in order to discover religious meaning in Serat Jasmaningrat manuscript. Results of the study show that the manuscript tells about the story of the journey of four people namely Ki Sarengat, Ki Tarekat, Ki Hakekat, and Ki Makrifat who went to the king at a palace. But, this story is actually telling about Sufism and the level of human being in relation with God. Hence, in the essence, the story is about Islamic Sufism.